On the origin of diffuse radio emission in Abell 85 – insights from new GMRT observations. Issue 2 (11th July 2022) - Rahaman, Majidul; Raja, Ramij; Datta, Abhirup; Burns, Jack O; Rapetti, David
ABSTRACT: Extended, steep, and ultra-steep spectrum radio emission in a galaxy cluster is usually associated with recent mergers. Simulations show that radio phoenixes are aged radio galaxy lobes whose emission reactivates when a low Mach shock compresses it. A85 hosts a textbook example of a radio phoenix at about 320 kpc southwest of the cluster centre. We present a new high-resolution 325 MHz GMRT radio map illustrating this radio phoenix's complex and filamentary structure. The full extent of the radio structure is revealed for the first time from these radio images of A85. Using archival Chandra X-ray observations, we applied an automated 2D shock finder to the X-ray surface brightness and Adaptive Circular Binning temperature maps that confirmed a bow shock at the location of the radio phoenix. We also compared the Mach number from the X-ray data with the radio-derived Mach number in the same region using multifrequency radio observations and find that they are consistent within the 1σ error level.